Determine the Effect of Different Levels of Nitrogen Treatment on Morphological and Physiological Parameters and Nitrates Accumulation of Lettuce Cultivars (Lactuca sativa L.) - M’hamdi, M.; Kalleli, F. (Current Research Progress in Agricultural Sciences Vol. 1, 2024)
The present study aimed to determine the effect of nitrogen treatment on (i) some agronomical parameters such as fresh and dry matter, root weight, leaf size and head diameter. (ii) physiological parameters: Chlorophyll fluorescence, sugar and nitrate content and its distribution in leaves. The effect of nitrogen fertilizer level on growth and nitrate accumulation was studied in six lettuce cultivars (Lactuca sativa L.): ‘Batavia rouge’, ‘Vitalia’, ‘Great Laks’, ‘Type Beurre’, ‘Romaine’ and ‘Romaine LO3’. Three nitrogen levels: 0, 120 and 240 Kg.ha-1 was applied. Agronomical (leaf weight, root weight, dry matter, head diameter) and physiological (nitrate concentration, chlorophyll fluorescence, and sugar content) characteristics were assessed as the plants grew. For the majority of agronomical and physiological indices, the results indicated significant variations between cultivars and nitrogen treatment. The nitrogen treatment affects head weight and nitrate concentration in all cultivars; the cvs ‘Great Laks’ and ‘Type beurre’ accumulated respectively the less and high nitrate concentration. The highest nitrate concentration was recorded in external leaves whereas the lowest concentration was recorded in the central leaves for all cultivars. Furthermore, nitrate distribution and chlorophyll fluorescence on the leaves are closely related. This study revealed also a correlation between root nitrate concentration, chlorophyll fluorescence and sugar content for all cultivars. This correlation depended on the nitrogen fertilization level and the cultivar used. More studies are required for the comprehension of the mechanisms of nitrate accumulation in leafy vegetables especially for the potential role of roots and its relationship with shoots.